Neo-Tethyan magmatism and metallogeny in Myanmar - An Andean analogue? - Gardiner, Nicholas; Searle, M.; Robb, L.; Morley, C. (2015)
© 2015 Elsevier Ltd. Plate margin tectonism, magmatic and hydrothermal processes, and the genesis of mineral deposits are intricately linked. In Myanmar two near-parallel magmatic belts, that together contain a significant proportion of that country's mineral wealth, have contrasting metallogenic endowments. The Mogok-Mandalay-Mergui Belt hosts crustal melt S-type granites with significant tin-tungsten mineralization, while the Wuntho-Popa Arc comprises I-type granites and granodiorites with copper-gold mineralization. The spatial juxtaposition of the two belts and their distinct but consistent metallogenic endowment bears strong similarities to the metallogenic belts of the South American Cordillera. Recent U-Pb age dating has shown the potential for the two belts to be near-contemporary from the Late Cretaceous to Eocene. Here we investigate whether an Andean-type setting during subduction of Neo-Tethys could explain the observed magmatism and mineralization within these two belts.